International review of blood donation nucleic acid amplification testing - Faddy, Helen M. (2024)
Background and Objectives Nucleic acid amplification testing (NAT), in blood services context, is used for the detection of viral and parasite nucleic acids to reduce transfusion-transmitted infections. This project reviewed NAT for screening blood donations globally. Materials and Methods A survey on NAT usage, developed by the International Society of Blood Transfusion Working Party on Transfusion-transmitted Infectious Diseases (ISBT WP-TTID), was distributed through ISBT WP-TTID members. Data were analysed using descriptive statistics. Results Forty-three responses were received from 32 countries. Increased adoption of blood donation viral screening by NAT was observed over the past decade. NAT-positive donations were detected for all viruses tested in 2019 (proportion of donations positive by NAT were 0.0099% for human immunodeficiency virus [HIV], 0.0063% for hepatitis C virus [HCV], 0.0247% for hepatitis B virus [HBV], 0.0323% for hepatitis E virus [HEV], 0.0014% for West Nile virus [WNV] and 0.00005% for Zika virus [ZIKV]). Globally, over 3100 NAT-positive donations were identified as NAT yield or solely by NAT in 2019 and over 22,000 since the introduction of NAT, with HBV accounting for over half. NAT-positivity rate was higher in first-time donors for all viruses tested except WNV. During 2019, a small number of participants performed NAT for parasites (Trypanosoma cruzi, Babesia spp., Plasmodium spp.). Conclusion This survey captures current use of blood donation NAT globally. There has been increased NAT usage over the last decade. It is clear that NAT contributes to improving blood transfusion safety globally; however, there is a need to overcome economic barriers for regions/countries not performing NAT.